Peningkatan Proses Pembelajaran Tematik Terpadu Dengan Menggunakan Model Problem Based Learning (PBL) Di Kelas IV SD Negeri 027962 Binjai - Anzani, Usi (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The purpose of this research is generally an integrated thematic learning process using the Problem Based Learning (PBL) model in class IV SD Negeri 027962 Binjai. The approach used is a qualitative and quantitative approach. This research was a class action research (CAR) which was carried out in two cycles, namely cycle 1 consisting of 1 meeting and cycle II consisting of 1 meeting. Each of these cycles includes four stages, namely planning, implementing, observing, and reflecting. The subjects of this study were teachers and students of Class IV SD Negeri 027962 Binjai with a total of 19 students, 9 boys and 10 girls. The results showed an increase in: Implementation of the teacher aspect of the first cycle with an average of 67.85% (enough) and 92.85% (very good) in the second cycle, while the implementation of the student aspects of the first cycle with an average of 64.28 (enough), and cycle II 89.28% (very good). Assessment of students in improving learning outcomes in cycle I was obtained with an average of 36.84% and cycle II with an average of 89.47%. Based on these results it can be concluded that the Problem Based Learning (PBL) model can improve the integrated thematic learning process in class IV.